PERANCANGAN SISTEM PENGUNCIAN RODA SATU ARAH UNTUK MENGEMUDIKAN KENDARAAN RODA EMPAT DI JALAN MENANJAK - Doni Helmahera; Dewa Made Wiharta; I Made Suartika (Jurnal SPEKTRUM, 2020)
Handbrake of a vehicle is the most important thing in a safety system in maintaining theposition of the vehicle in its stop position. The hand brakes function to brake or lock the rearwheels mechanically through the connecting rods and cables. The hand brake is also to parkthe vehicle on a down/climb road. In order to facilitate the ability of four-wheeled vehicles whenstopping on the ramp due to traffic jams, a special wheel locking system is used on the ramp. Ina one-way wheel shooting system when a four-wheeled vehicle stops on the ramp, the systemlocks the wheel when the wheel rotates slightly backwards without having to pull the handbrakelever. Therefore, this research aims to describe how the work of the one-way wheel lockingsystem when on the ramp of a four-wheeled vehicle. At the design of this system researchersmake prototype as a simulation system that is approaching similar to the shape of componentsof a four-wheeled vehicle. Researchers perform test system work when the prototype movesforward and backwards to find out if the system is capable of locking the wheels when the moveis backward and release the locking wheel when moving forward without using the hand brake.Using a one-way wheel locking system is expected to facilitate the driver in driving four-wheeledvehicles on the ramp without having to use the hand brake.